If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(1 + 9x) = 33 (1 * -6 + 9x * -6) = 33 (-6 + -54x) = 33 Solving -6 + -54x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -54x = 33 + 6 Combine like terms: -6 + 6 = 0 0 + -54x = 33 + 6 -54x = 33 + 6 Combine like terms: 33 + 6 = 39 -54x = 39 Divide each side by '-54'. x = -0.7222222222 Simplifying x = -0.7222222222
| 2p+15q=8 | | N-25=18+24 | | N-25=18+2 | | -3x^2-36x=0 | | 13+3r(4-1r)=5r-2 | | 2x+6y=19.80 | | -6p+3q=15 | | -2/7K=6/11 | | 4.5*.3+.7x=4 | | 3q-6p=15 | | -0.2222222222222222X-0.25=1.5-0.1666666666666667X | | 5b+3-7=17 | | -5x^3y/-15xy^3 | | 4x-7+5y-14=180 | | e=3t*3t*3t+2q*2q+t | | 3*(3x+4)=5*12-4*(2x-5) | | 10-5p=15p+(-6) | | 5/u-4=3 | | X-30=21 | | y+3x=25 | | 2-3(x+4)2=8 | | 9x+8x=60+20-12 | | 90+5x+3x+10=180 | | 2-3(x-4)2=8 | | 3-9cos(x)=x | | c=2k*2k+k-2k+6 | | 90+3y+11+y+7=180 | | 4x^2-7x-26=0 | | -15w+15=(-3w+3) | | 18x^2=6 | | 1/3-x/9-cosx | | b=4p*p+p*p |